Tourist Village Development Analysis after Pandemic Covid-19 as a Potency for Rural Resilience in Indonesia - S S Aulia (Peneliti.net, 2022)
Rural areas are very vulnerable areas with the Covid-19 pandemic due to the lack of infrastructure, especially health facilities. The Covid-19 pandemic has caused tourist activities in countries around the world, such as Indonesia, to decline due to large-scale social restrictions. One of the drivers of the non-agricultural economy in rural areas is tourism activities. Village tourism activities focus on natural tourism that is integrated with unique rural cultural tourism so that it becomes a tourist attraction. Research on the development of tourist villages in Indonesia after the Covid-19 pandemic as a form of potential for rural resilience is new research conducted. This research used qualitative analysis, utilizing review literature and secondary data. The development of tourist villages strongly related to the socio-ecological system in the village, such as the resilience of the tourist village community and the institutional ability.